Hypergravity Attenuates Reactivity in Primary Murine Astrocytes - Lichterfeld, Yannick; Kalinski, Laura; Schunk, Sarah; Schmakeit, Theresa; Feles, Sebastian; Frett, Timo; Herrmann, Harald; Hemmersbach, Ruth; Liemersdorf, Christian (Biomedicines, 2022)
Neuronal activity is the key modulator of nearly every aspect of behavior, affecting cognition, learning, and memory as well as motion. Hence, disturbances of the transmission of synaptic signals are the main cause of many neurological disorders. Lesions to nervous tissues are associated with phenotypic changes mediated by astrocytes becoming reactive. Reactive astrocytes form the basis of astrogliosis and glial scar formation. Astrocyte reactivity is often targeted to inhibit axon dystrophy and thus promote neuronal regeneration. Here, we aim to understand the impact of gravitational loading induced by hypergravity to potentially modify key features of astrocyte reactivity. We exposed primary murine astrocytes as a model system closely resembling the in vivo reactivity phenotype on custom-built centrifuges for cultivation as well as for live-cell imaging under hypergravity conditions in a physiological range (2g and 10g). We revealed spreading rates, migration velocities, and stellation to be diminished under 2g hypergravity. In contrast, proliferation and apoptosis rates were not affected. In particular, hypergravity attenuated reactivity induction. We observed cytoskeletal remodeling of actin filaments and microtubules under hypergravity. Hence, the reorganization of these key elements of cell structure demonstrates that fundamental mechanisms on shape and mobility of astrocytes are affected due to altered gravity conditions. In future experiments, potential target molecules for pharmacological interventions that attenuate astrocytic reactivity will be investigated. The ultimate goal is to enhance neuronal regeneration for novel therapeutic approaches.
CRIS-Team WoS Importer:2022-09-09